New chapters in the history of rhetoric - Pernot, Laurent. (International Studies in the History of Rhetoric, 2009)
This volume gathers over forty papers by leading scholars in the field of the history of rhetoric. It illustrates the current trends in this new area of research and offers a great richness of insights. The contributors are from fourteen different countries in Europe, America and Asia ; the majority of the papers are in English and French, some others in German, Italian, and Spanish. The texts and subjects covered include the Bible, Classical Antiquity, Medieval and Modern Europe, Chinese and Korean civilization, and the contemporary world. Word, speech, language and institutions are addressed from several points of view. One major topic, among many others, is Rhetoric and Religion.